Head injury and neuropsychiatric sequelae in asylum seekers. (10th November 2020) - McMurry, Hannah S.; Tsang, Darren C.; Lin, Nicole; Symes, Stephen N.; Dong, Chuanhui; Monteith, Teshamae S.
Abstract : Objective: Asylum seekers experience a high burden of physical and psychological trauma, yet there is a scarcity of literature regarding the epidemiology and sequelae of head injury (HI) in asylum seekers. We examined HI prevalence and association with neuropsychiatric comorbidities in asylum seekers. Methods: A retrospective cross-sectional study was performed through review of 139 medical affidavits from an affidavit database. Affidavits written from 2010 to 2018 were included. Demographic and case-related data were collected and classified based on the presence of HI. For neuropsychiatric sequelae, the primary study outcome was headache and the secondary outcomes were depression, posttraumatic stress disorder, and anxiety. Multivariable logistic regression was performed to examine the association between HI and neuropsychiatric sequelae, adjusted for demographic and clinical characteristics. Results: A total of 139 medical affidavits of asylum seekers were included. The mean age was 27.4 ± 12.1 years, 56.8% were female, and 38.8% were <19 years. Almost half (42.5%) explicitly self-reported history of HI. Compared to clients who did not report HI, clients with HI were older and more likely to report a history of headache, physical abuse, physical trauma, concussion, and loss of consciousness. After adjustment for demographic and clinical characteristics, clients with HI had greater odds for neuropsychological sequelae such as headache (odds ratio [OR] 4.2, 95% confidence interval [CI] 2.0–8.7) and depression (OR 2.5, 95% CI 1.1–5.7). Conclusions: We observed a high prevalence of HI in asylum seekers. Comprehensive screening for HI and neuropsychiatric comorbidities is encouraged when evaluating asylum seekers.